Design, synthesis and characterisation of novel organic conjugated materials - Saranya Asokan (2018)
Novel organic compounds have been constantly researched on to design and synthesize new compounds that benefit daily lives. These can contribute to the making of drugs, pesticides, fuel additives and various other areas. Tetracene, an organic semiconductor is widely researched on, and it can be used in organic field-effect transistors (OFET) and organic light-emitting diodes (OLED). In this project, the design, synthesis and characterization of 12-amino-2,7-di-tert-butyl-9,14-diphenyldibenzo[de,qr]tetracene-11carboxylic acid (ATD Tetracene) was done to produce a novel organic compound. The experimental procedures are included in the report, as well as the HRMS, 1HNMR and 13CNMR scheme and data were include for characterization.